Development of Real-Time and Colorimetric Loop Mediated Isothermal Amplification Assay for Detection of Xanthomonas gardneri - Stehlíková, Dagmar (Microorganisms, 2020)
Xanthomonas gardneri is one of the causal agents of bacterial spot (BS), an economically important bacterial disease of tomato and pepper. Field-deployable and portable loop-mediated isothermal amplification (LAMP)-based instruments provide rapid and sensitive detection of plant pathogens. In order to rapidly and accurately identify and differentiate X. gardneri from other BS-causing Xanthomonas spp., we optimized a new real-time monitoring LAMP-based method targeting the X. gardneri-specific hrpB gene. Specificity and sensitivity of real-time and colorimetric LAMP assays were tested on the complex of bacterial strains pathogenic to tomato and pepper and on plants infected by the pathogen. The assay detection limit was 1 pg/μL of genomic DNA with an assay duration of only 30 min. The use of portable and handheld instruments allows for fast analysis, reducing the diagnosis time, and can contribute to proper disease management and control of X. gardneri. Due to the high efficiency of this method, we suggest its use as a standard diagnostic tool during phytosanitary controls.